Re-introduction of financial literacy to the team members of Sol Victoria’s Tagaytay Branch - Mojica, Paolo Brando M. (Animo Repository, 2022)
This Action Research focuses on the re-introduction of the concept of financial literacy to the team members of Sol Victoria's Tagaytay - branch. Living conditions in the Philippines made it a challenge for simple individuals to save and invest their hard-earned money. There are a lot of factors that contribute to this problem. We ask the question “Does Financial literacy matter?” As mentioned by Lusardi, “financial literacy affects everything from day-to-day to long-term financial decisions, and this has implications for both individuals and society. Low levels of financial literacy across countries are correlated with ineffective spending and financial planning, and expensive borrowing and debt management” (p.6). As time goes by, we are also witnessing how these financial services evolve. There are fresh financial concepts that are being introduced to us. It is just right that we know the foundations to be able to understand these new products and services. Guided by the methodology of the Action Research cycle, and through the collaborations of the team members and me, a change was implemented. This resulted in positive reactions which hopefully will have a long-term effect on their financial practices.